Review On Scope And Challenges Of Direct Seeded Rice In Nepal - Adhikari, BB (Agronomy Journal of Nepal, 2021)
Rice is an important staple food crop of more than half of the population in the world to provide food security and livelihoods. Imminent water crisis due to climate change, water demanding nature of traditionally cultivated rice, increasing scarcity of labor and escalating labor costs drive the search for alternative management methods to increase water productivity, system sustainability and profitability in rice cultivation. Direct seeded rice (DSR) technique has received much attention and popularity nowadays because of its low-input demanding nature that can mitigate emission of green-house gases and adaption to climatic risks. DSR involves sowing of dry seed into a prepared seedbed, pre-germinated seed into a puddled soil surface and standing water. The development of early maturing varieties and use of efficient nutrient management practices along with increased adoption of integrated weed management techniques have encouraged many farmers to switch from transplanted to DSR culture. DSR technology is highly mechanized in some developed countries like USA, Australia, Japan, China, Korea etc. This shift from traditional rice to DSR will substantially reduce crop water requirements, soil organic-matter turnover, enhanced nutrient management, carbon sequestration, weed management, greenhouse-gas emissions and enhance crop intensification. However, weed and nematode infestation, blast, panicle sterility, lack of suitable varieties for DSR and lodging are major challenges. Based on existing evidences, this paper reviews the integrated package of technologies for DSR, potential advantages and challenges associated with it.